2016
DOI: 10.1152/ajpgi.00314.2015
|View full text |Cite
|
Sign up to set email alerts
|

Rapid disruption of intestinal epithelial tight junction and barrier dysfunction by ionizing radiation in mouse colon in vivo: protection byN-acetyl-l-cysteine

Abstract: The goals of this study were to evaluate the effects of ionizing radiation on apical junctions in colonic epithelium and mucosal barrier function in mice in vivo. Adult mice were subjected to total body irradiation (4 Gy) with or without N-acetyl-l-cysteine (NAC) feeding for 5 days before irradiation. At 2-24 h postirradiation, the integrity of colonic epithelial tight junctions (TJ), adherens junctions (AJ), and the actin cytoskeleton was assessed by immunofluorescence microscopy and immunoblot analysis of de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
102
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(111 citation statements)
references
References 37 publications
7
102
0
Order By: Relevance
“…In the present study, NAC treatment reduced the damage to intestinal integrity and the mucus barrier (Fig. ), consistent with the findings of a recent study in which NAC protected radiation‐induced mice against disruption of intestinal tight junctions and barrier dysfunction …”
Section: Discussionsupporting
confidence: 93%
“…In the present study, NAC treatment reduced the damage to intestinal integrity and the mucus barrier (Fig. ), consistent with the findings of a recent study in which NAC protected radiation‐induced mice against disruption of intestinal tight junctions and barrier dysfunction …”
Section: Discussionsupporting
confidence: 93%
“…31 An irradiated colonic epithelium displayed a rapid redistribution of tight junctional complexes in the acute phase. 4 However, in this in vivo and in vitro study, rebamipide was able to prevent the irradiation-induced destruction of TJs in the colonic epithelium. These findings suggested that the TJ recovery upon rebamipide treatment attenuated the radiation-induced colonic damage.…”
Section: Discussionmentioning
confidence: 63%
“…The condition may also lead to alterations of the gut microbiota and induce colonic endotoxemia. 4,25 Therefore, we focused on the effects of rebamipide against colonic injury using a GI-ARS model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations